Analysis of the Effect of Energy Consumption on Can Size Variations in Tuna Canning - Akbar Maulana; M. Effendi (International Journal of Health Engineering and Technology, 2025)
This study analyzes the effect of can size variations on energy consumption during the vacuum process in canned tuna production. The background for this research is the high energy intensity of the canning industry, driven by rising production costs and the need for greater environmental sustainability. The study's objective was to quantify the relationship between can size, headspace volume, and the energy required for vacuuming, a specific gap in existing literature. A quantitative experimental method was employed, with a population of canned tuna products from a single facility and a sample of three can sizes: 301×102 (70 g), 211×109 (95 g), and 307×112 (185 g). Data was collected using direct observation and operational records, with analysis performed via descriptive statistics and an ANOVA test. Results showed significant differences in energy consumption, with larger cans requiring higher steam pressure but demonstrating greater overall efficiency per gram of product. The 185 g can was found to be the most optimal choice, exhibiting the highest packaging efficiency and lowest coal consumption per gram, while also maintaining the best microbiological quality. The study concludes that can size is a critical factor for optimizing energy costs and product quality in mass production.